ANALISIS POTENSI PRODUKSI BIOETANOL DARI PRIESTIA FLEXA JT4 MENGGUNAKAN ZOBELL MARINE BROTH DENGAN CEKAMAN SALINITAS SECARA AEROBIK - Harvi Mulyani, Ravina
The relatively high demand for fuel depends on the availability of non-renewable resources, namely fossils. The use of these resources has various negative impacts, especially in terms of health and environment. Therefore, other sources are needed to replace fossil-based energy, one of which is the use of lignocellulosic biomass for bioethanol production by bioconversion processes by microorganisms. However, the bioconversion process requires large amounts of water which is met by using river water or sea water. Seawater desalination is considered less profitable because it is expensive and unsustainable. For this reason, research on bioethanol production in salty environments needs to be carried out. This study analyzed the production of bioethanol from the halotolerant bacteria Priestia flexa JT4 at two variations of NaCl concentration, namely 2 and 10% (w/v). Cultivation of Priestia flexa JT4 was carried out in Zobell marine broth medium for 96 hours at 130 rpm agitation and room temperature. The initial inoculum concentration used was 107 CFU/mL (10%(v/v)). In this study, it was observed that the growth pattern of Priestia flexa JT4 was divided into three phases namely lag, exponential and stationary. The specific growth rate and generation time in the control and stress treatments were respectively 0,103/hour; 6,80 hours; 0,037/hour; and 18,67 hours. Substrate consumption patterns were found to decrease with increasing biomass. In contrast, the pattern of ethanol production increases with the increase in the amount of biomass. The rate of consumption of carbon sources in the control and stress treatments were respectively 6.61 mg/L/hour and 7.21 mg/L/hour. The highest bioethanol yield was in the control and stress treatments respectively, namely 64.89 mg/L and 84.14 mg/L. Product gain on biomass (YP/X) in the control and biomass treatments respectively were 0,04 and 0,03g/g. Thus, it can be concluded that the application of NaCl stress at a concentration of 10% (w/v) can increase bioethanol production. The productivity of bioethanol obtained in the stress treatment was 0.88 mg/L/hour.